Effect Of Sowing Dates On Year Round Production Of Foliage Of Coriander (Coriandrum sativum L.) (Bangladesh Journal of Agricultural Research, 2013)
Four genotypes of coriander (CS001, CS002, CS003, and CS004) were planted at twenty different dates starting from 01 March 2008 at 15 days interval to 15 February 2009 at the research farm of the Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur to assess the genotypes for year round production of foliage of coriander. It revealed that the number of plants/m2 and foliage yield/ha decreased with the increase of temperature. The 01 January 2009 sowing gave the maximum foliage yield (6.38 t/ha) followed by 01 December 2008 sowing (6.05 t/ha). The genotype CS003 was the best yielder followed by CS001 and CS002. Performances of genotypes were the poorest during hot periods i.e. 01 April 2008 to 01 October 2008. The genotypes CS001, CS002 and CS003 performed better with regard to foliage production from 01 September 2008 to 15 February 2009 and in 15 March 2008, while the genotype CS008 gave better result from 15 October 2008 to 01 February 2009. Bangladesh J. Agril. Res. 38(1): 29-39, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15187